Manual de los Reglamentos del Agua en Florida: Manejo de Desechos Sólidos - Michael T. Olexa; Luke D'Isernia; Laura Minton; Dulcy Miller; Sarah Corbett (EDIS)
Revised! This series is the Spanish language version of the Handbook of Florida Water Regulations by Michael T. Olexa, Luke D'Isernia, Laura Minton, Dulcy Miller y Sara Corbett. Published by the UF Department of Food and Resource Economics, November 2006.